Radiation protection and structural stability of fungal melanin polylactic acid biocomposites in low Earth orbit - Radames J. B. Cordero; Kim K. de Groh; Quigly Dragotakes; Saranshu Singla; Christopher Maurer; Andrew Trunek; Arlene Chiu; Jonghyun Hwang; Sylvie Crowell; Theresa Benyo; Susanna M. Thon; Lynn J. Rothschild; et al. (Proceedings of the National Academy of Sciences, 2025)
Materials in low Earth orbit (LEO) face radiation, atomic oxygen erosion, and extreme temperature fluctuations, which can severely compromise their structural and functional integrity. Developing lightweight, multifunctional materials capable of withstanding these harsh conditions is critical for long-term space exploration and sustainable extraterrestrial settlements. This study evaluates the structural stability and radiation shielding efficacy of polylactic acid (PLA) and biocomposites, including PLA infused with fungal melanin, synthetic melanin, or animal melanin, and a compressed mycelium (CMy) coated with PLA (PLA-CMy), after exposure to the LEO environment. Samples were deployed on the Materials International Space Station Experiment–Flight Facility platform for approximately 6 mo in zenith- and wake-facing orientations. Postflight analyses comparing flight-exposed samples to Earth controls revealed composition- and orientation-dependent differences in mass loss, optical properties, and surface morphology. Notably, fungal melanin reduced mass loss and surface wrinkle formation, indicating a protective effect against PLA degradation in LEO. Biocomposites also demonstrated shielding effects by protecting an underlying polyvinyl chloride backing layer from damage. These findings demonstrate PLA’s performance in space and highlight fungal melanin as a bioderived additive to enhance PLA resilience under LEO conditions, advancing the development of sustainable materials for future space missions.